Survey on multipath TCP congestion control - Pei LIU; Yong-mao REN; Jun LI (Tongxin xuebao)
First，several congestion control algorithms of multipath TCP recently had been introduced and discussed.Next,some simulation experiments in NS2 was did,the performance of MPTCP congestion control algorithm in TCP fairness of the bottleneck link,resource pooling and flapness was analyzed.At last,some problems existed and possible research directions in the future was pointed out.